Steam Generator Production Engineering:Depth Version of CC - Neelameghan, A.; Gopinath, M. A. (Journal of Information and Knowledge, 1971)
A freely-faceted depth classification version of Colon Classification for compound subjects going with the Host Subject "D8, D4h Steam Generator Production Engineering" is given. The use of different devices-such as, Geographical Device, Environment Device, Numerical Device, and Alphabetical Device-has helped in achieving economy in schedule building. An index to the schedule, eleven examples of subjects classified and an alphabetical index to the subjects are given. The pattern of incidence of Quasi Isolates is commented upon.